An analysis of the measurement principle of smart brackets for 3D force and moment monitoring in orthodontics - Rues, Stefan; Panchaphongsaphak, B.; Gieschke, P.; Paul, O.; Lapatki, B. G. (Journal of biomechanics, 2011)
Measuring the three-dimensional (3D) force-moment (F/M) systems applied for correcting tooth malposition is highly desirable for accurate spatial control of tooth movement and for reducing traumatic side effects such as irreversible root resorption. To date, suitable tools for monitoring the applied F/M system during therapy are lacking. We have previously introduced a true-scale orthodontic bracket with an integrated microelectronic stress sensor system for 3D F/M measurements on individual teeth with a perspective for clinical application. The underlying theoretical concept assumes a linear correlation between externally applied F/M systems and mechanical stresses induced within the smart bracket. However, in combined applications of F/M components the actual wire-bracket contacts may differ from those caused by separate applications of corresponding individual F/M components, thus violating the principle of linear superposition of mechanical stresses. This study systematically evaluates this aspect using finite element (FE) simulations and measurements with a real smart bracket. The FE analysis indicated that variability in the wire-bracket contacts is a major source for measurement errors. By taking the critical F/M combinations into account in the calibration of the real smart bracket, we were able to reduce the mean measurement error in five of the six F/M components to values <0.12N and <0.04Ncm. Bucco-lingually directed forces still showed mean errors up to 0.21N. Improving the force measurement accuracy and integrating components for telemetric energy and data transfer are the next steps towards clinical application of intelligent orthodontic appliances based on smart brackets.